Histopathology of vaccine‐preventable diseases. Issue 1 (January 2017) - Solomon, Isaac H; Milner, Danny A
Abstract : The widespread use of vaccines has been one of the most important medical advances in the last century, saving trillions of dollars and millions of lives. Despite local eradication of some infections, travellers returning from affected areas may cause outbreaks through reintroduction of pathogens to individuals who are unable to receive vaccines for medical reasons or who have declined vaccination for non‐medical reasons. Infections that would otherwise be uncommonly encountered by anatomical pathologists should therefore remain in the differential diagnosis for immunocompromised and unvaccinated patients. We review here the histopathological features and ancillary testing required for diagnosis of all illnesses preventable by vaccines that are currently approved for use by the United States Food and Drug Administration, organized into three sections: viral infections preventable by routine vaccination (measles, mumps, rubella, varicella, rotavirus, polio, hepatitis A, hepatitis B, influenza, and human papillomavirus), bacterial infections preventable by routine vaccination (diptheria, tetanus, pertussis, Haemophilus influenzae, pneumococcus, and meningococcus), and infections with specific vaccine indications (anthrax, typhoid, tuberculosis, rabies, Japanese encephalitis, yellow fever, smallpox, and adenovirus). Histopathology for the less common diseases is illustrated in this review. Awareness of a patient's immune and/or vaccine status is a crucial component of the infectious disease work‐up, especially for rare diseases that may not otherwise be seen.